A light-initiated chemical reporter strategy for spatiotemporal labeling of biomolecules. Issue 5 (8th April 2022) - Wang, Feifei; Kong, Hao; Meng, Xiangfeng; Tian, Xiao; Wang, Changjiang; Xu, Lei; Zhang, Xiang; Wang, Lei; Xie, Ran
Abstract : Combination bioorthogonal chemical reporter strategy and photo-reaction enables imaging of newly-synthesized glycans, lipids and proteins with spatiotemporal resolution. Abstract : The emergence of optochemical approaches has had a diverse impact over a broad range of biological research due to spatiotemporal regulation. Herein, we integrate this feature into the bioorthogonal chemical reporter strategy, which enables visible light-controlled spatiotemporal labeling of cell-surface glycans, lipids, and proteins. The metabolic precursors were first incorporated into live cells, and next the bioorthogonal reaction converted the azide/alkyne into a photo-active functional group, which allowed for subsequent photo-click reaction. We demonstrated this strategy by specifically labeling sialome, mucin-type O -glycome, phospholipids and newly-synthesized membrane proteins, respectively. The sequential photoirradiation-orthogonal reporter tagging (SPORT) should facilitate the probing of biomolecules in complex biological systems with high spatiotemporal precision.